The in vitro effects of black soldier fly larvae (Hermitia illucens) oil as a high-functional active ingredient for inhibiting hyaluronidase, anti-oxidation benefits, whitening, and UVB protection - Phongpradist, Rungsinee; Semmarath, Warathit; Kiattisin, Kanokwan; Jiaranaikulwanitch, Jutamas; Chaiyana, Wantida; Chaichit, Siripat; Phimolsiripol, Yuthana; Dejkriengkraikul, Pornngarm; Ampasavate, Chadarat (Frontiers in Pharmacology, 2023)
Objective: Larvae of Hermitia illucens, or black soldier fly larvae (BSFL), have been recognized for their high lipid yield with remarkable fatty acid profile. BSFL oil (SFO) offers the added value of a low environmental footprint and a sustainable product. In this study, the characteristics and cosmetic-related activities of SFO were investigated and compared with rice bran oil, olive oil and krill oil which are commonly used in cosmetics and supplements.The physicochemical characteristics were determined including acid value, saponification value, unsaponifiable matter and water content of SFO. The fatty acid composition was determined using GC-MS equipped with TR-FAME. The in vitro antioxidant properties were determined using DPPH, FRAP and lipid peroxidation inhibition assays. Antihyaluronidase (anti-HAase) activity was measured by detecting enzyme activity and molecular docking of candidate compounds toward the HAase enzyme. The safety assessment towards normal human cells was determined using the MTT assay and the UVB protection upon UVB-irradiated fibroblasts was determined using the DCF-DA assay. The whitening effect of SFO was determined using melanin content inhibition.Results: SFO contains more than 60% polyunsaturated fatty acid followed by saturated fatty acids (up to 37%). The most abundant component found in SFO was linoleic acid (C18:2 n-6 cis). Multiple antioxidant mechanisms of SFO were discovered. In addition, SFO and krill oil prevented hyaluronic acid (HA) degradation via strong HAase inhibition comparable with the positive control, oleanolic acid. The molecular docking confirmed the binding interactions and molecular recognition of major free fatty acids toward HAase. Furthermore, SFO exhibited no cytotoxicity on primary human skin fibroblasts, HaCaT keratinocytes and PBMCs (IC50 values >200 g/mL). SFO possessed significant in-situ antioxidant activity in UVB-irradiated fibroblasts and the melanin inhibition activity as effective as wellknown anti-pigmenting compounds (kojic acid and arbutin, p <0.05).This study provides scientific support for various aspects of SFO. SFO can be considered an alternative oil ingredient in cosmetic products with potential implications for anti-skin aging, whitening and UVB protection properties, making it a potential candidate oil in the cosmetic industry.Black soldier fly larvae (Hermitia illucens) oil: a high-functional active ingredient for inhibiting hyaluronidase, anti-oxidation benefits, whitening, and UVB protection